Pc-C10: An innovative carbon allotrope with concurrent metallic conductivity and exceptional mechanical property - Lingyu Liu; Yan Zhuang; Mengdong Ma; Li Zhu; Pan Ying; Meng Hu; Yueqing Li; Julong He; Qinyong Zhang (Journal of Materials Research and Technology)
Carbon, renowned for its versatility in bonding and structural diversity, has long been a focal point of materials research. Despite extensive studies on carbon allotropes, a significant challenge remains: the development of carbon materials that combine both exceptional mechanical properties and electrical conductivity. Here, we propose a novel sp2-sp3 hybridized tetragonal carbon allotrope Pc-C10 via first-principle calculations. This structure is more energetically favorable than graphite at pressures above 55 GPa, suggesting the potential for synthesis via high-pressure phase transitions. Our results show that Pc-C10 not only exhibits metallic conductivity through a quasi-one-dimensional conducting channels but also demonstrates superconductivity with a critical temperature of 0.25 K. This new carbon structure displays remarkable mechanical properties, including a hardness of 26 GPa, tensile and shear strengths over 80 GPa for outstanding resistance to deformation and fracture. In particular, a unique damage-self-repair-strengthening behavior is displayed during shear. The combination of these distinctive properties makes this novel carbon material a promising candidate for future applications in electronics, superconductivity, and structural materials technology.